RNA and Toll-Like Receptor 7 License the Generation of Superior Secondary Plasma Cells at Multiple Levels in a B Cell Intrinsic Fashion - Krueger, Caroline C.; Thoms, Franziska; Keller, Elsbeth; Leoratti, Fabiana M. S.; Vogel, Monique; Bachmann, Martin F. (Frontiers in Immunology, 2019)
Secondary plasma cells (PCs) originate from memory B cells and produce increased levels of antibodies with higher affinity compared to PCs generated during primary responses. Here we demonstrate that virus-like particles (VLPs) only induce secondary PCs in the presence of toll-like receptor (TLR) 7 and if they are loaded with RNA. Furthermore, adoptive transfer experiments demonstrate that RNA and TLR7 signaling are required for secondary PC generation, both at the level of memory B cell as well as PC differentiation. TLR7-signalling occurred in a B cell intrinsic manner as TLR7-deficient B cells in an otherwise TLR7-competent environment failed to differentiate into secondary PCs. Therefore, RNA inside VLPs is essential for the generation of memory B cells, which are competent to differentiate to secondary PCs and for the differentiation of secondary PCs themselves. While we have not tested all other TLR or non-TLR adjuvants with our VLPs, these data have obvious implications for vaccine design, as RNA packaged into VLPs is a simple way to enhance induction of memory B cells capable of generating secondary PCs.